Dynamic transitions of initiator binding coordinate the replication of the two chromosomes in Vibrio cholerae - Théophile Niault; Ariel Talavera; Eric Le Cam; Sonia Baconnais; Ole Skovgaard; Florian Fournes; Léa Wagner; Hedvig Tamman; Andrew Thompson; Dannele Echemendia-Blanco; Noa Guzzi; Abel Garcia-Pino; et al. (Nature Communications)
Abstract The replication of the two chromosomes in the pathogenic bacterium Vibrio cholerae is coordinated by the binding of initiator protein RctB to a checkpoint sequence, crtS. Replication of crtS on the primary chromosome (Chr1) triggers replication of the secondary chromosome (Chr2), but the details are poorly understood. Here, we analyze RctB binding patterns in the V. cholerae genome across various cell cycle stages. We find that RctB primarily binds to sites inhibiting replication initiation at the Chr2 origin (ori2). This inhibitory effect is counteracted when crtS is replicated on Chr1, causing a shift in RctB binding to sites that activate replication at ori2. Structural analyzes indicate the formation of diverse oligomeric states of RctB, coupled to the allosteric effect of DNA, which determine ori2 accessibility. We propose a synchronization model where, upon replication, crtS locally destabilizes the RctB inhibition complex, releasing the Chr2 replication origin.